Ressources humaines - Gantet, Laurent; Poirot-Delpech, Matthieu; Lespert, Jalil; Vallod, Jean-Claude; Barré, Chantal (Arte Video, 2000)
Franck (Jalil Lespert) returns from business school in Paris to his provincial home town, where he takes up the post of trainee in the personnel department of the factory where his father has worked for 30 years. At that time, the government's 35-hour-week is about to be implemented. Relations between management and workers is aggravated by a combative Communist union leader. Franck suggests taking the problem direct to the shop floor with a referendum, designed to discover the feelings of the workforce behind the backs of organised labour. Of course, it isn't as simple as that. The boss flatters Franck, when it suits him, while using the young man's sharper intellect for his own ends. The workers are suspicious of anything emanating from management and his father sees nothing wrong with a boring, repetitive job. Cantet's cast of unemployed workers makes acting look easy. Lespert, as the only professional, pulls off a remarkable feat. Franck is basically a dull boy, who studied hard at college. The stand he takes at the factory, where loyalties are divided, requires guts. Lespert follows Franck's evolution from swot to rebel, without ever allowing himself the satisfaction of becoming a hero. [www.eyeforfilm.co.uk]